Upstream-Downstream Influence of Water Harvesting Techniques (Jessour) on Soil Water Retention in Southeast Tunisia - Calianno, Martin; Ben Fraj, Tarek; Fallot, Jean-Michel; Abbassi, Mohamed; Ghram Messedi, Aziza; Ben Ouezdou, Hédi; Reynard, Emmanuel (MDPI, 2023)
Weather parameters and soil moisture profiles were measured at an hourly time step during four agricultural years (September to October, from 2018–19 to 2021–22) in two Jessour (water harvesting cultivated terraces) of the same valley in Zmerten (southeastern Tunisia), characterized by an arid climate. One instrumented Jesr (singular of Jessour) was located upstream and the other one downstream. During each dry season, when crops experience water stress, the downstream Jesr had a higher available water content than the upstream one; in the downstream Jesr the soil profile moisture remained above the wilting point, whereas in the upstream soil surface, moisture levels decreased to below the wilting point. High accumulation/low intensity rains (causing saturation/excess runoff) flooded both upstream and downstream Jessour from 50 mm of cumulative rainfall, whereas high intensity/low accumulation rains (causing infiltration/excess runoff) activated the downstream Jesr from an intensity of 15.2 mm/h, and a combination of moderate intensity and moderate accumulation rains activated both Jessour from an intensity of 8 mm/h and a cumulative rainfall of 33 mm. We propose to set 50 mm of cumulative rainfall and/or 6.4 mm/h of intensity as threshold values for the activation of the Jessour system in Zmerten. However, significant soil moisture recharges can occur even without activation of the Jessour system.